The effect of Klotho protein complexed with nanomaterials on bone mesenchymal stem cell performance in the treatment of diabetic ischaemic ulcer - Rui Tang; Gang Zhao; Yuqiao Wang; Ruixue Zhang (IET Nanobiotechnology)
Abstract A lack of angiogenesis is the key problem in the healing of diabetic foot ulcers. Stem cells have already been proven to have a high potential for angiogenesis. The most important aspects of stem cell therapy are improving the microenvironment, cell homing and continuous factor stimulation. We investigated the effect of Klotho protein to heal wounds by promoting the proliferation and migration of bone mesenchymal stem cells and endothelial cells in vitro. Based on the above study, we produced a compound material by using poly(lactic‐co‐glycolic acid) (PLGA), chitosan microspheres and gelatin through electro spining technology. The structure of the compound material, just like a sandwich, is that two pieces of PLGA nanofiber films clamped gelatin film which contained chitosan microspheres. In the in vitro release experiment, we could detect the release of Klotho after seven days in the compound material, but the release time was approximately 40 hours for the chitosan microspheres. After seeded bone mesenchymal stem cells (BMSCs) on the surface of the compound material, we observed morphologies of the chitosan microsphere, the PLGA nanofiber and BMSCs by scanning electron microscopy. The nanofiber mesh biological tissue materials could supply an appropriate microenvironment and cell factors for the survival of BMSCs. Compared with the control group, the biological tissue material seeded with BMSCs significantly promoted angiogenesis in the lower limb of diabetic C57BL/6J mice and accelerated diabetic foot wound healing. The compound biomaterial which could continuously stimulate BMSCs through releasing Klotho protein could accelerate wound healing in the diabetic foot and other ischemic ulcers.